(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2022)
This paper seeks to re-democratise poetry-making as a creative and therapeutic act, much in the way that visual art has been welcomed into the therapy room. What is the creative impulse to turn thought into language? And how can paying attention to it help our clients in their attempts to make meaning?